A fuzzy based load frequency control and load shedding scheme for islanded distribution network connected with mini-hydro /Javed Ahmed Laghari - Javed, Ahmed Laghari (2012)
Mini hydro power plant (MHPP) based DG is cost effective and environmental friendly resource for rural electrification schemes. The DG can be connected in parallel with grid to supply the increased load demand. However, in utility practice when load disturbance occurs in grid, DG is tripped-off. Due to this, DG capacity is not utilized efficiently. In order to utilize the DG capability, islanding need to be done. The islanding has a considerable advantage such as reliability improvement, blackout reduction. However, islanding operation is a challenging issue; if there is any unbalanced between load demand and power generation, the system frequency will change. The system frequency is maintained by controlling the turbine speed through governor. If governor fail to stabilize the frequency, load shedding techniques needs to be applied in order to maintain distribution network stability and security. PID based governor have the problem of obtaining optimum parameter tuning. In order to cope this, fuzzy logic control technique may be an option to provide robust and quick control. This research proposes fuzzy based governor for load frequency control (LFC) of MHPP, and compares its response with PID based governor to show its superiority. Apart from this, this research proposes a fuzzy based under frequency load shedding (UFLS) scheme applied in an islanded distribution network connected with DG. The proposed under frequency load shedding scheme consists of a fuzzy logic load shedding controller (FLLSC) and load shed controller module (LSCM). FLLSC estimates amount of power imbalance and sends this value to LSCM for shedding the required load. Both Event-based and Response based under frequency load shedding cases are modelled and tested on base load and peak load capacity. The fuzzy based under frequency load shedding scheme is designed to shed optimal load in the system.